Urolithiasis Associated Morbidity in Children - Aamer Mehmood Khan,Muhammad Shahid Hussain,Khemchand N Moorani , Khalid Mehmood Khan (Journal of Rawalpindi Medical College, 2014)
Background : To determine the various types of medical complications associated with urolithiasis in children. Methods: In this descriptive study 60 children of 1 month to 12 years age with haematuria, abdominal pain, history of passing stone or retention of urine and confirmed as suffering from renal calculi on radiological examination were selected. Initial investigations included urine routine examination, culture and sensitivity, blood urea, serum creatinine, serum electrolytes, plain x-ray Kidney, Ureter and Bladder and ultrasound for KUB. Further investigation like IVP, MCUG, nuclear scans such as DTPA, DMSA , MAG3 and metabolic screening for stones were done where required. Results: Majority (66%) were boys, with male: female ratio 2:1. Acute renal failure was present in 33% of the patients, and urinary tract infections in 23% of the patients. Many patients had more than one complication. Calculus anuria was seen in 3(5%) patients. Hypertension and urosepsis were observed in 1.6%, each. Fifteen patients had calcium stones and six patients had oxalate stones Conclusion: Acute renal failure is the most common renal complication which can be prevented with early diagnosis and management.